Käsien puutuminen - Avikainen, Veikko J. (Duodecim : lääketieteellinen aikakauskirja, 1998)
Tiivistelmä.
Keywords: kädet; puutuminen; hoito; diagnostiikka; händer; domning; vård; diagnostik; erotusdiagnoosi; yläraaja; hermo; pinne; sormi